Alpha‐synuclein aggregates activate calcium pump SERCA leading to calcium dysregulation - Betzer, Cristine (EMBO Rep, 2018)
Aggregation of α‐synuclein is a hallmark of Parkinson's disease and dementia with Lewy bodies. We here investigate the relationship between cytosolic Ca(2+) and α‐synuclein aggregation. Analyses of cell lines and primary culture models of α‐synuclein cytopathology reveal an early phase with reduced cytosolic Ca(2+) levels followed by a later Ca(2+) increase. Aggregated but not monomeric α‐synuclein binds to and activates SERCA in vitro, and proximity ligation assays confirm this interaction in cells. The SERCA inhibitor cyclopiazonic acid (CPA) normalises both the initial reduction and the later increase in cytosolic Ca(2+). CPA protects the cells against α‐synuclein‐aggregate stress and improves viability in cell models and in Caenorhabditis elegans in vivo. Proximity ligation assays also reveal an increased interaction between α‐synuclein aggregates and SERCA in human brains affected by dementia with Lewy bodies. We conclude that α‐synuclein aggregates bind SERCA and stimulate its activity. Reducing SERCA activity is neuroprotective, indicating that SERCA and down‐stream processes may be therapeutic targets for treating α‐synucleinopathies.